PEMBERIAN HORMAX DAN NPK MUTIARA 16:16:16 PADA TANAMAN UBI JALAR ( Ipomoea batatas L.) - Budiman Manurung; Siti Zahrah; Zulkifli (DINAMIKA PERTANIAN, 2018)
ABSTRACT The purpose of this study was to determine the effect of Hormax and NPK Mutiara (16:16:16) on sweet potato plants. The design used in this study was a Factorial Complete Randomized Design consisting of two factors. The first factor is Hormax (H) at doses of 0, 1, 3, and 5 ml per liter of water while the second factor is NPK Mutiara (16:16:16) (N) with concentrations of 0, 3.15, 6.3, and 9.45g per plant. The parameters observed were the number of crop tubers (tubers), tuber weight per plot (g), tuber weight per tuber (g), tuber weight per plant (g), wet pruned weight (g), harvest index. The last observation data were analyzed statistically and continued with a BNJ follow-up test at the 5% level. The results showed that the interaction of giving Hormax and NPK Mutiara (16:16:16) significantly affected the number of tubers per plant, tuber weight per plot, tuber weight per fruit, weight. The best treatment is in the combination of H2N2 fertilizer concentration of 3 ml/liter of water and 6.3 g / plant. The main influence of hormax is evident on the parameters of the number of tubers per plant, tuber weight per plot, tuber weight per tuber, tuber weight per plant, wet perched weight, harvest index, the best treatment of 3 ml per liter of water (H2). The main effect of NPK Mutiara fertilizer (16:16:16) is real on the parameters of the number of tubers per plant, tuber weight per plot, tuber weight per fruit, tuber weight per plant, wet perched weight, harvest index, best treatment ie 6.3 g per plants (N2). Keywords: Hormax, NPK, Sweet Potatoes